Impact of pharmacological and behavioral interventions on post- traumatic headache in children: a literature review - Nunes, Melyssa Maria Fernandes da Rocha; Lousada, Lívio Martins; Pinheiro, Giulia Rebouças; Azevedo, Marina Pinheiro Uchoa; Soares, Ana Clara Mendes; Coutinho, Isadora Pinheiro; Filho, Otavio Pereira da Silva; Moura, Lucas Eliel Beserra (Headache Medicine, 2023)
Full abstract in PDF.